Regulation of biological control agents - Ehlers, Ralf-Udo (Springer, 2011)
This book presents a comprehensive compilation of registration requirements necessary for authorisation of biological control agents (viruses, bacteria, fungi, active substances of natural origin and semiochemicals) in OECD countries. It also reviews data requirements for invertebrate agents (insect, mites and nematodes) and provides proposals for harmonisation of the regulation process and guidelines for completion of application forms. Based on results of the EU REBECA Policy Support Action, which gathered experts from academia, regulation authorities and industry, risks and benefits of the specific agents were reviewed and proposals for a more balanced registration process elaborated, including recommendations for acceleration of the authorisation process and discussions on trade-off effects and policy impacts. All these aspects are covered in detail in this book, which points the way forward for enhanced utilisation of biological control agents.